17.0k views
3 votes
Solve for c. a(c + b)=d
c=d − ab/b
c=d + ab/a
c=ab − d/a
c=d − ab/a

User Alcalde
by
5.4k points

2 Answers

7 votes

Answer:

c = (d - ab) / a

Explanation:

a(c + b) = d // We multiply a by c and b (addition is distributive)

ac + ab = d // We let the c addend in the left

ac = d - ab // We divide by a

c = (d - ab) / a

User Jay Thummar
by
5.7k points
3 votes

Answer: Hi Hi I know this is like a year late but I would like to be able to help future people with this question.

The correct answer is: c=d+ab/a (B)

Isolate the variable by dividing each side by factors that don't contain the variable.

I really hope this helps people, have a happy halloween :D

User Shivam
by
5.3k points